(3GdJHUQI aj Yde GdgjFIs - (3CHh eMeO YHO GdLHGQ Hf YHO GdLHGQ Hf eMeO GdKGHJj GdNQbj,J (B553 (3g` s ((3CHh fUQ Hf CHj GdSQhQ GdeJWHH s)
(3ChdgG (B:s
(3hgj GdRgQI hYWGQO hGdbeQ Chdi GdChVGY hGdeQGJH hLYdhgG cTeSI GdbdGOI ai GdfXe hGdJQJjH GdHGH GdKGdK ai PcQ GdHQGgjf Ydi cQjI GdCadGc s
(3BNQgG (B:s
(3hGdefLehf jbSehf cd SGYI ef GdSGYGJ HSJjf bSekG , cd bSe ObjbI ; Ydi eG LQJ YGOJge ai bSeI GdHQhL hCLRGFgG HGdCLRGA GdSJjfjI adfNJe GdcJGH EPG CJjfG HGdehYhO Ydi MSH GdebOhQ hGdhGgH GdYbd GdMeO HdG fgGjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3HgG fXGe GdJYbjHIs
(3LOGhd hQShe gfOSjI hadcjI HBNQgG ai (B19 (3hQbI ef hQbI (B111-129 (3JYdjb bje Ydi cJGH GdJHUQI ai Yde GdgjFI ddNQbi cJH HNWg dfaSg CHh fUQ Hf CHj GdSQhQ hgh GdfGSN dds
(3fSNI KGfjIs
(3jJab BNQgG eY BNQ GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdadcs